2019
DOI: 10.1158/1078-0432.ccr-18-1580
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Resistance against the MDM2 Inhibitor RG7388 in Glioblastoma Cells by the MEK Inhibitor Trametinib

Abstract: Purpose: Resistance is an obstacle of glioma therapy. Despite targeted interventions, tumors harbor primary resistance or become resistant over short course of treatment. This study examined the mouse double minute 2 (MDM2) inhibitor RG7388 together with radiotherapy and analyzed strategies to overcome acquired MDM2 inhibitor resistance in glioblastoma.Experimental Design: Effects of RG7388 and radiotherapy were analyzed in p53 wild-type glioblastoma cell lines and glioma-initiating cells. RG7388 resistant cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 41 publications
0
47
1
Order By: Relevance
“…The attenuation of p53 functions in GBM patients has been attributed to post-translational regulation of the p53 protein, whose levels are tightly controlled by the E3 ubiquitin ligase MDM2 through proteasomal degradation 28. Elevated levels of MDM2 protein impair wildtype p53 function and accelerate tumor growth in various human cancers, including leukemia, sarcoma, breast cancer, melanoma, and GBM 7, 29-32. Nevertheless, MDM2 also transfers ubiquitin to itself, resulting in self-destruction 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attenuation of p53 functions in GBM patients has been attributed to post-translational regulation of the p53 protein, whose levels are tightly controlled by the E3 ubiquitin ligase MDM2 through proteasomal degradation 28. Elevated levels of MDM2 protein impair wildtype p53 function and accelerate tumor growth in various human cancers, including leukemia, sarcoma, breast cancer, melanoma, and GBM 7, 29-32. Nevertheless, MDM2 also transfers ubiquitin to itself, resulting in self-destruction 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although p53 can be produced constitutively, it is negatively regulated by the mouse double minute 2 (MDM2) protein that binds to the transcription activation domain of p53, thereby inhibiting acetylation, stimulating nuclear export, and most importantly, promoting proteasomal degradation via MDM2's E3 ubiquitin ligase activity 6. The tumor-promoting effect of MDM2 in GBMs has been reported in prior publications 7.…”
Section: Introductionmentioning
confidence: 97%
“…Although the DNA profile of the U87‐MG cells was found to be different from that of the original cells, it was likely a bona fide human GBM cell line of unknown origin . Many studies have successfully illustrated the pathogenesis of GBM and the pharmacological function of new pharmaceutical products on GBM with the U87‐MG cell line in recent years . In this study, we developed a concise and reliable analysis through combining our transcriptome analyses on U87‐MG and HEB cells with established databases and in vitro and ex vivo experiments, which successfully revealed a set of core pathways in GBM cells under normoxic and hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…in recent years, studies have reported the signaling pathway inhibitors have synergistic effects on radiotherapy and chemotherapy, which can significantly enhance the sensitivity of cancer therapy (27)(28)(29). lee et al (30) have demonstrated that lY294002 improves the sensitivity of cervical cancer cells to radiotherapy in a significant time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%